The effects of zeolite on milk production and composition, rumen parameters and digestibility of the diets - M. Ali Azman; H. Derya Umucalılar; Emin Arat; A. İhsan Akın (Eurasian Journal of Veterinary Sciences)
This study was earned out to determine Ihe effects of zeolite (Cli-nut/1000) in dairy cattle ration and 16 lactating Brown Swiss cattle were used. Six percent ot zeolite was added to the concentrate diet in test group. In the research was determined dry matter intake, milk production performance, rumen pH, total volatile fatty acids (TVFA). ammonia nitrogen (NH3-N). crude protein and crude ftber digestibility. In the experiment, dry matter intake, milk production were found in control and test groups 14.97 and 14.17 kg/day. 15.66 and 16.37 kg/day, respectively and there was no significant difference between groups (P>0.05). In control and test groups, average milk dry matter, fat. protein were determined 12.26 and 12.14%. 3.94 and 3.76%, 3.34 and 3.29% (P>0.05). At the end of the research. Ihe addition of zeolite did not influence mean ruminal pH. ammonia nitrogen and total VFA concentration which were detected 6 88 and 6.88, 183.6 and 217,2 mmol/l, 139.2 and 129.2 mmol/1, respectively (P>0.05). Estimates of crude protein and fiber digestibilities in test group (67,63% , 69.95%) were lower than control (72.70%, 77.39%) and crude fiber digestibility was found significant difference between groups (P<0.05).